Fracionamento de melitina a partir da apitoxina por ultrafiltração com escoamento tangencial - Evelin Campos Verdolin Brandão (2019)
Apitoxin, bee venom, has been used for years as a medicine for various inflammatory diseases. The benefits of this venom are mainly provided by melittin, which is present with other high allergenic potential components, phospholipase A2 (PLA2) and hyaluronidase, for example. Thereby, the separation of melittin from apitoxin becomes feasible, since it is a desired product in the pharmaceutical and cosmetic industries also has a high added value. Hence, ultrafiltration with a tangential flow and commercial membrane of regenerated cellulose of 10 kDa was used as a separation method, in order to reach a concentration of permeate with the smallest fraction of these allergenic compounds. In the first step, a 2² factorial design with triplicate at the central point was performed to investigate the effects of apitoxin concentration and pressure difference on permeate flow, melittin recovery, and PLA2 rejection, in which was defined the optimal working condition: lower concentration - 1.0 mg / mL - and the highest pressure - 1.5 bar. Based on these results, the second step was carried out to evaluate the flux decline during ultrafiltration and the incrustation mechanisms present in the process using the modified Hermia model. Hereafter, a chemical cleaning was performed after completing all experiments. As a result, the permeate flux decline was mostly caused by fouling because of several mechanisms acting without a more precise definition. The membrane cleaning depicted a recovery of 91.69% in the permeate flux and reduce 94.10% of resistance. Finally, it may be concluded that ultrafiltration using tangential flow has been an attractive option for the separation of melittin from apitoxin.